2013
DOI: 10.1101/gad.233254.113
|View full text |Cite
|
Sign up to set email alerts
|

Multiple small RNA pathways regulate the silencing of repeated and foreign genes in C. elegans

Abstract: Gene segments from other organisms, such as viruses, are detected as foreign and targeted for silencing by RNAi pathways. A deep-sequencing map of the small RNA response to repeated transgenes introduced to Caenorhabditis elegans revealed that specific segments are targeted by siRNAs. Silencing of the foreign gene segments depends on an antiviral response that involves changes in active and silent chromatin modifications and altered levels of antisense siRNAs. Distinct Argonaute proteins target foreign genes f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 72 publications
4
47
1
Order By: Relevance
“…Consistent with the known role of these four genes in transgene silencing (Yigit et al, 2006, Grishok et al, 2005, Fischer et al, 2013, Yang et al, 2014, Shirayama et al, 2014, Shiu et al, 2014), expression of the GFP reporter was significantly enhanced in all four mutants, but in no mutant was significant pharyngeal silencing in the first-generation observed (Figure 1B). RDE-1, an Argonaute essential for primary siRNA maturation (Steiner et al, 2009, Sijen et al, 2001), is required for second-generation pharyngeal muscle silencing (Figure 1C).…”
Section: Resultssupporting
confidence: 79%
“…Consistent with the known role of these four genes in transgene silencing (Yigit et al, 2006, Grishok et al, 2005, Fischer et al, 2013, Yang et al, 2014, Shirayama et al, 2014, Shiu et al, 2014), expression of the GFP reporter was significantly enhanced in all four mutants, but in no mutant was significant pharyngeal silencing in the first-generation observed (Figure 1B). RDE-1, an Argonaute essential for primary siRNA maturation (Steiner et al, 2009, Sijen et al, 2001), is required for second-generation pharyngeal muscle silencing (Figure 1C).…”
Section: Resultssupporting
confidence: 79%
“…As HOOD assembly depends on RNAi, Pab2, cryptic introns and splicing factors (Lee et al, 2013; Yamanaka et al, 2013), it is plausible that CCR4-NOT and Pir2 are recruited by splicing factors (and EMC at certain loci) and cooperate with RNAi to assemble HOODs. Supporting this idea, it has been shown that: (1) ARS2 interacts with Dicer in Drosophila and Arabidopsis and is involved in RNAi (Sabin et al, 2009; Yang et al, 2006); (2) C. elegans ntl-9 , a subunit of CCR4-NOT, is required to generate siRNAs from its endogenous targets (Fischer et al, 2013); and (3) human ARS2 co-purifies with the spliceosome (Rappsilber et al, 2002). Alternatively, Pir2 may facilitate HOOD assembly through non-canonical transcription termination.…”
Section: Discussionmentioning
confidence: 99%
“…In fission yeast, the Ccr4-Not complex was recently shown also to be involved in deposition of H3K9 methylation at rDNA and meiotic genes (Cotobal et al 2015;Sugiyama et al 2016). Additionally, the Ccr4-Not complex was shown to play a role in silencing of subtelomeric transposons in Caenorhabditis elegans and Drosophila melanogaster (Fischer et al 2013;Morgunova et al 2015). Transposons are targeted by piRNAs in animal germline cells that establish heterochromatin in a similar way to siRNAs in fission yeast (Hirakata and Siomi 2016).…”
Section: Discussionmentioning
confidence: 99%